Engineering Potato Virus X Particles for a Covalent Protein Based Attachment of Enzymes. Issue 48 (10th November 2017) - Röder, Juliane; Fischer, Rainer; Commandeur, Ulrich
Abstract: Plant virus nanoparticles are often used to display functional amino acids or small peptides, thus serving as building blocks in application areas as diverse as nanoelectronics, bioimaging, vaccination, drug delivery, and bone differentiation. This is most easily achieved by expressing coat protein fusions, but the assembly of the corresponding virus particles can be hampered by factors such as the fusion protein size, amino acid composition, and post‐translational modifications. Size constraints can be overcome by using the Foot and mouth disease virus 2A sequence, but the compositional limitations cannot be avoided without the introduction of time‐consuming chemical modifications. SpyTag/SpyCatcher technology is used in the present study to covalently attach the Trichoderma reesei endoglucanase Cel12A to Potato virus X (PVX) nanoparticles. The formation of PVX particles is confirmed by western blot, and the ability of the particles to display Cel12A is demonstrated by enzyme‐linked immunosorbent assays and transmission electron microscopy. Enzymatic assays show optimal reaction conditions of 50 °C and pH 6.5, and an increased substrate conversion rate compared to free enzymes. It is concluded that PVX displaying the SpyTag can serve as new scaffold for protein display, most notably for proteins with post‐translational modifications. Abstract : Potato virus X, a plant virus, is engineered to display the SpyTag . Together with its counterpart SpyCatcher, an enzyme is covalently attached to the surface. This system overcomes limitations arising from proteins that cannot be expressed as genetic fusions, e.g., target proteins that are too large, those with an inappropriate amino acid composition or those carrying post‐translational modifications.